STUDI PENYIMPANAN ENERGI PADA BATERAI PLTS - Redaksi Tim Jurnal (Energi & Kelistrikan, 2017)
The use of fossil fuels such as petroleum, coal and others as a fuel for conventional plants has an impact on the environment. Environmental impacts that occur such as environmental pollution from the greenhouse effect (greenhouse effect) that causes global warming, acid rain, the destruction of the ozone layer to the loss of tropical forests. With the condition of the need for renewable energy in the fossil energy era is running thinning at this time making the use of solar energy to meet human needs for energy to be the right choice. The use of solar energy becomes an option because of the nature of the source of solar energy that will not run out, and its easy use and application compared to other renewable energy sources. PLTS maintenance support becomes very important when PLTS has been installed. In Solar Power Generation, energy storage systems need special attention because they involve continuous energy availability especially during cloudy or late night when there is no sunlight. In this research will be discussed about the study of energy storage on PLTS battery. This characteristic is influenced by several things such as weather conditions and duration of irradiation on an area that affect the value of light intensity, voltage (V), current (I) and power that can be caused. From the research found that installed solar panels can generate power 1553,82 watts for 9 hours of solar radiation for one day.